PENGARUH SHIFT KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL MELIA MAKASSAR - Virza Hadrianti (Pusat Penelitian dan Pengabdian kepada Masyarakat Universitas Dipa Makassar, 2024)
This study aims to determine the effect of work shifts and work discipline on employee performance at the Melia Makassar Hotel. The approach used in this study is quantitative. The population in this study were employees of the Melia Makassar Hotel, with a population of 75 people who were used as saturated samples in this study. The technique used in data collection was a survey method in the form of a questionnaire which was then processed using the SPSS application. The results of the study that has been conducted regarding the effect of work shifts and work discipline on employee performance at the Melia Makassar Hotel, can be concluded that work shifts and work discipline have a significant effect on employee performance. By improving the existing work shift system and encouraging high work discipline, hotels can create a more productive and efficient work environment.